Ocean leadership: Can the European Union influence the global shark meat trade? - A. Ospina-Alvarez; S. de Juan; C. Cáceres; U.R. Sumaila; G. Sant; N.K. Dulvy; C.A. Simpfendorfer; R. García; S. Niedermüller; S. Villasante (Marine Policy, 2025)

Shark depredation: future directions in research and management - J. D. Mitchell; J. M. Drymon; J. Vardon; P. G. Coulson; C. A. Simpfendorfer; S. B. Scyphers; S. M. Kajiura; K. Hoel; S. Williams; K. L. Ryan; A. Barnett; M. R. Heupel; et al. (Reviews in Fish Biology and Fisheries, 2023)
Shark depredation is a complex social-ecological issue that affects a range of fisheries worldwide. Increasing concern about the impacts of shark depredation, and how it intersects with the broader context of fisheries management, has driven recent research in this area, especially in Australia and the United States. This review synthesises these recent advances and provides strategic guidance for researchers aiming to characterise the occurrence of depredation, identify the shark species responsible, and test deterrent and management approaches to reduce its impacts. Specifically, the review covers the application of social science approaches, as well as advances in video camera and genetic methods for identifying depredating species. The practicalities and considerations for testing magnetic, electrical, and acoustic deterrent devices are discussed in light of recent research. Key concepts for the management of shark depredation are reviewed, with recommendations made to guide future research and policy development. Specific management responses to address shark depredation are lacking, and this review emphasizes that a “silver bullet” approach for mitigating depredation does not yet exist. Rather, future efforts to manage shark depredation must rely on a diverse range of integrated approaches involving those in the fishery (fishers, scientists and fishery managers), social scientists, educators, and other stakeholders.

Genetic diversity of Australian Fusarium pseudograminearum populations causing crown rot in wheat - Mohammed Khudhair; F. Obanor; K. Kazan; D. M. Gardiner; E. Aitken; A. McKay; D. Giblot-Ducray; S. Simpfendorfer; L. F. Thatcher (European Journal of Plant Pathology, 2021)

Phytophthora root rot of chickpea: inoculum concentration and seasonally dependent success for qPCR based predictions of disease and yield loss - S.L. Bithell; K. Moore; Herdina; A. McKay; S. Harden; S. Simpfendorfer (Australasian Plant Pathology, 2021)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Crown rot of wheat in Australia: Fusarium pseudograminearum taxonomy, population biology and disease management - S. Alahmad; S. Simpfendorfer; A. R. Bentley; L. T. Hickey (Australasian Plant Pathology, 2018)

Evaluation of fungicide timing and preventative application on the control of Fusarium head blight and resulting yield - S. Simpfendorfer (Australasian Plant Pathology, 2016)

Highly heritable resistance to root-lesion nematode (Pratylenchus thornei) in Australian chickpea germplasm observed using an optimised glasshouse method and multi-environment trial analysis - M. S. Rodda; K. B. Hobson; C. R. Forknall; R. P. Daniel; J. P. Fanning; D. D. Pounsett; S. Simpfendorfer; K. J. Moore; K. J. Owen; J. G. Sheedy; J. P. Thompson; G. J. Hollaway; et al. (Australasian Plant Pathology, 2016)

Variation in blacktip shark movement patterns in a tropical coastal bay - S. E. M. Munroe; C. A. Simpfendorfer; M. R. Heupel (Environmental Biology of Fishes, 2016)

Sequential application of hyperspectral indices for delineation of stripe rust infection and nitrogen deficiency in wheat - R. Devadas; D. W. Lamb; D. Backhouse; S. Simpfendorfer (Precision Agriculture, 2015)

Regional movement patterns of a small‐bodied shark revealed by stable‐isotope analysis - S. E. M. Munroe; M. R. Heupel; A. T. Fisk; M. Logan; C. A. Simpfendorfer (Journal of Fish Biology, 2015)
This study used stable‐isotope analysis to define the nearshore regional residency and movements of the small‐bodied Australian sharpnose shark Rhizoprionodon taylori . Plasma and muscle δ 13 C and δ 15 N of R. taylori were collected from across five embayments and compared with values of seagrass and plankton from each bay. Linear distances between adjacent bays ranged from 30 to 150 km. There was a positive geographic correlation between R. taylori tissue and environmental δ 13 C values. Populations with the highest tissue δ 15 N were collected from bays that had the highest environmental δ 15 N values. These results suggest that R. taylori did not forage more than 100 km away from their capture location within 6 months to 1 year. The successful application of isotope analysis to define R. taylori movement demonstrates that this technique may be used in addition to traditional methods to study the movement of sharks, even within similar habitats across regionally small spatial scales (

Defining shark ecological specialisation: concepts, context, and examples - S. E. M. Munroe; C. A. Simpfendorfer; M. R. Heupel (Reviews in Fish Biology and Fisheries, 2014)

A review of detection range testing in aquatic passive acoustic telemetry studies - S. T. Kessel; S. J. Cooke; M. R. Heupel; N. E. Hussey; C. A. Simpfendorfer; S. Vagle; A. T. Fisk (Reviews in Fish Biology and Fisheries, 2014)

Introgression of hexaploid sources of crown rot resistance into durum wheat - A. Martin; S. Simpfendorfer; R. A. Hare; M. W. Sutherland (Euphytica, 2013)

Comparative biology of tropical Lethrinus species (Lethrinidae): challenges for multi‐species management - L. M. Currey; A. J. Williams; B. D. Mapstone; C. R. Davies; G. Carlos; D. J. Welch; C. A. Simpfendorfer; A. C. Ballagh; A. L. Penny; E. M. Grandcourt; A. Mapleston; A. S. Wiebkin; et al. (Journal of Fish Biology, 2013)
Life‐history characteristics of six tropical Lethrinus species sampled from the Great Barrier Reef World Heritage Area were compared. Two species groups were identified based on fork length ( L F ): large species with maximum L F > 640 mm (longface emperor Lethrinus olivaceus , yellowlip emperor Lethrinus xanthochilus and spangled emperor Lethrinus nebulosus ) and small species with maximum L F 480 mm (Pacific yellowtail emperor Lethrinus atkinsoni , pink ear emperor Lethrinus lentjan and ornate emperor Lethrinus ornatus ). Lifespan was not correlated with L F . Early growth for all species was rapid and similar during the first few years of life, but coefficients of the von Bertalanffy growth function varied considerably among species. Growth also differed between sexes for L. atkinsoni . Reproductive characteristics varied among species, with peak periods of spawning occurring in November to December for L. atkinsoni , July to August for L. nebulous , September to October for L. olivaceus and a protracted season for L. lentjan , although fewer samples were available for the last two species. Sex‐specific L F and age distributions and gonad histology of L. lentjan were suggestive of a functional protogynous reproductive pattern, as observed in other lethrinids. Gonad histology indicated non‐functional protogynous hermaphroditism for L. atkinsoni and L. nebulosus . The diversity of life histories among these closely related species emphasizes the difficulty in devising single management strategies appropriate for multi‐species fisheries and illustrates the importance of understanding species‐specific life histories to infer responses to exploitation.

Genetic tools to support the conservation of the endangered smalltooth sawfish, Pristis pectinata - Kevin A. Feldheim; Demian D. Chapman; Colin A. Simpfendorfer; Vincent P. Richards; Mahmood S. Shivji; Tonya R. Wiley; Gregg R. Poulakis; John K. Carlson; Rowena Eng; Skyler Sagarese (Conservation Genetics Resources, 2010)

Evaluating ten spectral vegetation indices for identifying rust infection in individual wheat leaves - R. Devadas; D. W. Lamb; S. Simpfendorfer; D. Backhouse (Precision Agriculture, 2009)

Pathogen population structure and epidemiology are keys to wheat crown rot and Fusarium head blight management - S. Chakraborty; C. J. Liu; V. Mitter; J. B. Scott; O. A. Akinsanmi; S. Ali; R. Dill-Macky; J. Nicol; D. Backhouse; S. Simpfendorfer (Australasian Plant Pathology, 2006)

Ascosporic and conidial inoculum of Gibberella zeae play different roles in Fusarium head blight and crown rot of wheat in Australia and the USA - V. Mitter; L. J. Francl; S. Ali; S. Simpfendorfer; S. Chakraborty (Australasian Plant Pathology, 2006)

Occurrence of Fusarium head blight (FHB) in southern NSW in 2000: identification of causal fungi and determination of putative chemotype of Fusarium graminearum isolates by PCR - M. K. Tan; S. Simpfendorfer; D. Backhouse; G. M. Murray (Australasian Plant Pathology, 2004)

Viability and pathogenicity of Phytophthora clandestina after storage in water and liquid nitrogen - S. Simpfendorfer; T.J. Harden; G.M. Murray (Australasian Plant Pathology, 1996)